Implementasi Pembelajaran Menggunakan Aplikasi Quizizz di SMP Ma'arif 2 Ponorogo: Muhamad Syaif Al-Ifkhan, Rizki Avandi Ramadani, Rizky Yoga Wibowo, Sindy Vita Aryani, Zuhrotul Murtafi’ah, Nurul Malikah - sindy vita aryani (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This study discusses the implementation of the Quizizz application in the learning process at SMP Ma'arif 2 Ponorogo, aiming to increase students' motivation and interest in learning. Research methods include observation, interviews, and literature studies, with a focus on mentoring the use of learning technology. The results of the study indicate that Quizizz is effective in creating an interactive, fun, and efficient learning atmosphere, despite obstacles such as limited devices and internet networks. Teachers overcome these challenges through various strategies, such as gradual training for students and optimization of existing resources. The benefits of using Quizizz include increasing student competence in cognitive aspects and efficiency of learning evaluation. In addition, this application also supports teacher creativity in managing technology-based learning. This study recommends the development of intensive training to improve teachers' abilities in utilizing educational technology.